Upregulation of Mitochondrial Content in Cytochrome c Oxidase Deficient Fibroblasts - Kogot-Levin, Aviram; Saada, Ann; Leibowitz, Gil; Soiferman, Devorah; Douiev, Liza; Raz, Itamar; Weksler-Zangen, Sarah (PLOS ONE, 2016)
Cytochrome-c-oxidase (COX) deficiency is a frequent cause of mitochondrial disease and is associated with a wide spectrum of clinical phenotypes. We studied mitochondrial function and biogenesis in fibroblasts derived from the Cohen (CDs) rat, an animal model of COX deficiency. COX activity in CDs-fibroblasts was 50% reduced compared to control rat fibroblasts (P<0.01). ROS-production in CDs fibroblasts increased, along with marked mitochondrial fragmentation and decreased mitochondrial membrane-potential, indicating mitochondrial dysfunction. Surprisingly, cellular ATP content, oxygen consumption rate (OCR) and the extracellular acidification rate (ECAR) were unchanged. To clarify the discrepancy between mitochondrial dysfunction and ATP production, we studied mitochondrial biogenesis and turnover. The content of mitochondria was higher in CDs-fibroblasts. Consistently, AMPK activity and the expression of NRF1-target genes, NRF2 and PGC1-α that mediate mitochondrial biogenesis were increased (P<0.01 vs control fibroblast). In CDs-fibrobalsts, the number of autophagosomes (LC3+ puncta) containing mitochondria in CDs fibroblasts was similar to that in control fibroblasts, suggesting that mitophagy was intact. Altogether, our findings demonstrate that mitochondrial dysfunction and oxidative stress are associated with an increase in mitochondrial biogenesis, resulting in preservation of ATP generation.